2017
DOI: 10.1111/jog.13198
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative assessment of factors associated with difficulty in performing total laparoscopic hysterectomy

Abstract: We have elucidated the factors associated with difficult TLH patients using patients' background and preoperative MRI findings. Awareness of these predictive factors may enable surgeons to prepare for the operation, minimize complications, or choose another more appropriate route of hysterectomy than TLH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The procedure performed in five included studies was vaginal hysterectomy. 14,17,29,32,33 Ten of the remaining included studies assessed the odds of surgical complications following minimally invasive hysterectomy (laparoscopic-assisted vaginal hysterectomy, total laparoscopic hysterectomy, and roboticassisted hysterectomy) 16,[20][21][22][23]27,28,31,34,35 and 11 included studies assessed the odds of various types of hysterectomy including total abdominal hysterectomy and vaginal hysterectomy. 4,6,15,18,19,[24][25][26]30,36,37 Study designs of the included studies were cohort studies (24) 4,6,14-25,27-29,31-37 and case-control studies (two) 26,30 (Tables S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure performed in five included studies was vaginal hysterectomy. 14,17,29,32,33 Ten of the remaining included studies assessed the odds of surgical complications following minimally invasive hysterectomy (laparoscopic-assisted vaginal hysterectomy, total laparoscopic hysterectomy, and roboticassisted hysterectomy) 16,[20][21][22][23]27,28,31,34,35 and 11 included studies assessed the odds of various types of hysterectomy including total abdominal hysterectomy and vaginal hysterectomy. 4,6,15,18,19,[24][25][26]30,36,37 Study designs of the included studies were cohort studies (24) 4,6,14-25,27-29,31-37 and case-control studies (two) 26,30 (Tables S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment among 24 cohort studies using the Newcastle-Ottawa Scale indicated that high risks for comparability and outcome assessment were, respectively, noted in 15 [14][15][16][17][18][21][22][23][24][25]27,28,33,34,36 and 12 studies. 6,14,15,17,18,22,27,29,31,33,34,37 No cohort study was judged as having a high risk of selection bias. The two case-control studies 26,30 included in this review were determined as having low-to-moderate risks of bias for all items.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, type 2 adenomyosis may be a good therapeutic target for long‐term dienogest administration. In addition, we previously reported that type 2 adenomyosis increased the difficulty of laparoscopic hysterectomy because of severe adhesion due to pelvic endometriosis . Therefore, long‐term dienogest administration may be beneficial to avoid difficult hysterectomy for patients with type 2 adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…When surgical intervention is necessary, total laparoscopic hysterectomy (TLH) is the preferred surgical treatment, and it has been found that reducing the uterine volume can expand the indications for and reduce the difficulty of TLH. [ 14 ] Therefore, preventing an increase in uterine volume should be considered as a high priority in the treatment of this condition. Previous reports have shown that GnRHa significantly reduces adenomyosis volume,[ 7 ] but there have been no definitive reports on the effects of LEP therapy on uterine volume in patients with adenomyosis.…”
Section: Discussionmentioning
confidence: 99%